Quantitative HBV/HDV markers help to distinguish different clinic/virologic phases of chronic hepatitis delta. (March 2023) - Ricco, G.; Cavallone, D.; Oliveri, F.; Colombatto, P.; Damone, F.; Coco, B.; Vianello, B.; Romagnoli, V.; Salvati, A.; Surace, L.; Bonino, F.; Brunetto, M.R.
Abstract : Introduction and aim: New therapy options for Chronic hepatitis delta (CHD) urge a better clinical/virologic stratification of patients(pts). We quantified HDV/HBV markers to investigate their correlation with disease activity/stage in untreated and Interferon(IFN)-treated pts. Methods: One hundred forty-six consecutive anti-HDV+pts admitted at Pisa University Hospital were classified based on biochemical/histological/imaging data in:1)Pts without liver disease (no-CHD)[ALT<40U/L, LS<6kPa];2)CHD without cirrhosis;3)CHD with cirrhosis;4)CHD with advanced cirrhosis [varices/decompensation/HCC]. HDV-RNA (RoboGeneKit2.0;Roboscreen-Diagnostics), anti-HDV(Liaison®XLmurexAnti-HDV, DiaSorin) and HBV markers (HBV-DNA/HBsAg/HBcrAg/anti-HBc-IgG) were tested at baseline(BL) in the overall cohort, and at end-of-therapy(EOT), 6-months after EOT (6mFU) and end-of-follow-up(EOF) in 31(21.2%) IFN-treated pts. Virologic response was defined by qualitative HDV-RNA (in house-PCR). Results: Table1 shows the BL characteristics of the overall cohort. Eleven (7.6%) subjects were classified as no-CHD; 10/11(90.9%) had HDV-RNA serum levels(sl)<1000 IU/mL. Among 135 CHD pts, HDV-RNA sl were higher in pts with cirrhosis compared to CHD without cirrhosis or with advanced cirrhosis. All no-CHD subjects had anti-HDV titer≤1:100; 132/135 CHD pts (97.8%) had anti-HDV≥1:1000. At multivariate analyses, HDV-RNA[OR=1.816/P=0.007], anti-HDV[OR=4.429/P=0.012] and anti-HBc-IgG[O7R=3.260/P=0.041] associated with higher disease activity(ALT>100U/L); Age[OR=1.059/P=0.032] and HDV-RNA [OR=1.643/P=0.006] associated with cirrhosis. Among 31 IFN-treated-pts [duration 12.4(2.0/91.7) months], 13(41.9%) had virologic response, 3 (9.7%) relapsed and 15(48.4%) were non-responders at 6mFU. At EOF [median 4.6(1.3-18)years], 14 pts maintained undetectable qualitative HDV-RNA and normal ALT, all of them showing HDV-RNA sl<1000 IU/mL, 12/14 (85.7%) anti-HDV≤1:100. The remaining pts with CHD at EOF had HDV-RNA sl>1000 IU/mL and anti-HDV≥1:1000 in 92.3% and 100% of cases, respectively. Conclusions: In CHD pts HDV-RNA sl independently correlate with biochemical activity and stage of liver disease. HDV infection can persist without active liver damage in a status, either spontaneously-acquired or IFN-induced, characterized by low levels of viral replication (HDV-RNA<1000 IU/mL) and anti-HDV titer (≤1:100) The quantitative analysis of HDV/HBV markers qualifies as a useful tool for clinic-virological classification and treatment monitoring of CHD pts.